Não-lugares como ambiente de serviço (servicescape): repensando a dimensão de serviços na perspectiva do cliente - Guido, Ana Lúcia Borella (2019)
The importance in contextualizing services by social aspects are considered study trends by Mari & Poggesi (2013), being culture one of the approached topics. As a theoretical contribution, this doctoral dissertation aims to investigate the concept of non-places, elaborated by Augé (1995) as a possible social element to be attached to services. As for administrative purposes, it is intended to contribute by mapping the determinants of service experience by the perspective of customers. User Generated Content (UGC) is applied as a data source for research and content analysis as a qualitative technique. Results indicate the possibility of systematizing services in the customer’s perspective. Regarding the theoretical inquiries about social approaches on culture Hofstede (2011) and non-places Augé (1995), results are inconclusive, what opens new avenues on such topic